2019
DOI: 10.3390/pharmacy7040168
|View full text |Cite
|
Sign up to set email alerts
|

Moving the Needle: A 50-State and District of Columbia Landscape Review of Laws Regarding Pharmacy Technician Vaccine Administration

Abstract: Pharmacy technicians are essential for inner workings of pharmacy teams and their depth of involvement in roles continues to evolve. An innovative role for pharmacy technicians, administration of vaccines, has emerged. With Idaho, Rhode Island, and Utah recently implementing changes that allow pharmacy technicians to safely perform this role, the need arose for a detailed examination of the law climate in all 50 states and the District of Columbia. A nine-question survey was sent out to all 51 state boards of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Washington State was chosen as the location for this research because it was previously identified as a state that did not yet have a specific administrative rule allowing technicians to immunize but it also did not expressly prohibit this practice. 8 Researchers were granted permission in advance from the pharmacy managers of these locations to conduct key informant interviews. By interviewing participants from pharmacies in Washington State, the researchers attempted to unveil the patient perceptions of immunizations provided by pharmacy technicians in a location in which technicians could begin immunizing in the near future.…”
Section: Project Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Washington State was chosen as the location for this research because it was previously identified as a state that did not yet have a specific administrative rule allowing technicians to immunize but it also did not expressly prohibit this practice. 8 Researchers were granted permission in advance from the pharmacy managers of these locations to conduct key informant interviews. By interviewing participants from pharmacies in Washington State, the researchers attempted to unveil the patient perceptions of immunizations provided by pharmacy technicians in a location in which technicians could begin immunizing in the near future.…”
Section: Project Designmentioning
confidence: 99%
“…7 Pharmacy technicians are allowed to administer immunizations in 3 states, namely Idaho, Rhode Island, and Utah, however, administration is not expressly prohibited in many other states. 8 Pharmacies use multiple approaches to reach those who need to be vaccinated, such as immunization clinics, community outreach programs, health fairs, ambulatory care clinics, events at long-term care facilities, corporate sites, community sites, travel health clinics, and medication therapy management encounters. In addition, pharmacies have convenient locations, flexibility, and extended work hours, and are often able to expand vaccine access to a population that may have limited access to other providers because of financial, geographic, or system barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Three states legally allow pharmacy technicians to administer immunizations [11][12][13]. Eid and colleagues assessed the regulatory nature of pharmacy technician vaccine administration with a nine-question survey sent to 51 state boards of pharmacy [14]. Findings demonstrated that, in addition to the three states where technicians were already allowed to immunize, nine other states did not expressly prohibit this advanced technician role [14].…”
Section: Introductionmentioning
confidence: 99%
“…The study authors recommend not only that technicians seek development opportunities in this area but also that pharmacists become more adept at the art of delegation and work with profession leaders to optimize appropriate staffing levels and skills mix of support personnel to advance practice. Eid et al pointed out that U.S. state board of pharmacy regulations were often overly prescriptive and favored the term "not expressly prohibited" in regard to many pharmacy technician roles [22]. This might be an improvement over them being previously being prohibited.…”
mentioning
confidence: 99%